Dampak Kartel Ayam Terhadap Struktur Pasar dan Persaingan Usaha di Indonesia: Analisis Ekonomi Pasca Kasus 2016 - Nadila Yunita Maharani; Naili Rachma Maulidya; Putu Oka Yadnya Susila; Muhammad Fatih Bustomi; Emma Yunika Puspasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The chicken cartel in Indonesia that was exposed in 2016 has become a major issue affecting market structure and corporate competition. This strategy involves 12 large companies collaborating to control the availability and price of chicken by limiting chicken production (parent stock). Using a descriptive approach and normative legal research methods, this study examines how the cartel affects market structure, corporate competitiveness, and consumer welfare. This study reveals that the chicken cartel encourages oligopolistic conditions that are detrimental to small producers, consumers, and the economy as a whole. Large companies dominate the market, causing consumers to pay unfair prices, while small farmers lose their competitiveness.